Risk Factors and Outcomes of Multidrug-resistant Pseudomonas aeruginosa in Kelantan, Malaysia: A Multicenter Case–control Study - Siti Norfairuz Md. Salim; Nurul Izzah Md Din; Rosnita Rashid; Sharifah Aisyah Sayed Hitam; Zakuan Zainy Deris (Saudi Journal of Medicine and Medical Sciences)
Background: Increasing trend and spread of multidrug-resistant Pseudomonas aeruginosa (MDR-PA) in clinical settings is a great challenge in managing patients with infections caused by this pathogen. Objective: To determine the risk factors and outcomes of MDR-PA acquisition in the northeastern state of Malaysia. In addition, this study also reported on the susceptibility pattern and common resistant genes among MDR-PA. Materials and Methods: MDR-PA isolates obtained between March 2021 and February 2022 from all four major hospitals in the state of Kelantan, Malaysia, were submitted for susceptibility and resistant genes identification. The clinical data of the patients with MDR-PA were retrospectively reviewed. The risk factors and outcomes of MDR-PA acquired patients were analyzed by comparing with patients who acquired susceptible-PA while admitted to the same hospital during the study time. Results: A total of 100 MDR-PA and 100 susceptible-PA cases were included. Ceftolozane–tazobactam was susceptible in 41.3% of MDR-PA compared to only 4%–8% with other β-lactams. About half (46%) of the MDR-PA isolates harbored the bla-NDM-1 gene, but none had the bla-OXA-48 gene. Factors independently associated with MDR-PA acquisitions were age (OR: 1.02; P = 0.028), genitourinary disorder (OR: 6.89; P = 0.001), and central venous catheter (OR: 3.18; P = 0.001). In addition, MDR-PA acquisitions were found to be associated with antimicrobial treatment failure (41.1% vs. 25.0%; P = 0.001) and mortality (40.0% versus 6.0%; P <0.001). Conclusion: Most of the MDR-PA strains in Kelantan tertiary hospitals harbored the bla-NDM-1 gene, which is easily transmissible and can lead to an outbreak. Nonetheless, a significant number of the MDR-PA isolates were still susceptible to ceftolozane–tazobactam.